I-Case Best Solution for 401K Team: Quick and Effective Impressed Twentieth Century Users - Eaton, Roger G. (My University, 2016)
The solution was not exactly gift-wrapped, but our investment management company was able to respond to a competitive market effectively with the help of an integrated CASE tool. By effectively, I mean the solution satisfied the user's requirements at the time it was implemented.
Citation: Eaton, R. (1994). I-Case Best Solution for 401K Team: Quick and Effective Impressed Twentieth Century Users. Application Development Trends: Business & Technology Solutions for Software Development, 1(5), 21-24
Keywords: CASE Tools; Computer Aided Software Engineering; Software Development; Relational Databases